CARRASCO, Lorenzo; LINO, Geraldo Luís; PALACIOS, Silvia. Máfia Verde: o ambientalismo a serviço do governo mundial. Rio de Janeiro: Capax Dei, 2020. - Montans Braga, Luiz Carlos (Revista de Geopolítica, 2024)
Resenha.